Clinical significance of hepatosplenic thrombosis in vaccine-induced immune thrombotic thrombocytopenia after ChAdOx1 nCoV-19 vaccination. (March 2022) - Hwang, Jimin; Han, Young Joo; Yon, Dong Keon; Lee, Seung Won; Kim, Beom Kyung; Lee, Se Bee; Lee, Min Ho; Park, Seung Hyun; Koyanagi, Ai; Jacob, Louis; Tizaoui, Kalthoum; Kim, Seung Up; et al.
Highlights: Hepatosplenic thrombosis was present in 17% of cases with VITT. Hepatosplenic thrombosis was associated with lower platelets and higher D-dimers. There was a higher rate of multiple site thrombosis with hepatosplenic thrombosis. Abstract: Background: Vaccine-induced immune thrombotic thrombocytopenia (VITT) is a rare, serious complication after adenoviral COVID-19 vaccine administration that can involve various organ systems. We aimed to investigate the clinical significance of hepatosplenic thrombosis in patients with VITT. Methods: We searched PubMed ePubs, Scopus, Embase, and Web of Science databases for studies published until April 28, 2021, involving patients with VITT after ChAdOx1 nCoV-19 vaccination. Demographic and clinical characteristics, including laboratory measurements, were collected and compared. Results: Four case series and three case reports involving 48 cases of VITT were included. Hepatosplenic thrombosis was present in 8 cases (17%). Patients with hepatosplenic thrombosis had lower platelet counts (13, 000 vs. 29, 500/μL, p =0.016) and higher D-dimer levels (140.0 vs. 57.3 times upper limit of normal range, p =0.028). Multiple-site thrombosis was also associated with hepatosplenic thrombosis (88% vs. 15%, p <0.001). Conclusions: This is the first study comparing clinical profiles of patients with VITT according to the presence of hepatosplenic thrombosis. Patients with hepatosplenic thrombosis had more severe presentations with lower platelet counts, higher D-dimer levels, and a higher rate of multiple-site thrombosis. Further studies with larger sample sizes are required to establish definitive evidence regarding the significance of hepatosplenic thrombosis in VITT.